2016
DOI: 10.18632/oncotarget.8225
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab combined with concurrent chemoradiotherapy in locally advanced nasopharyngeal carcinoma: a retrospective analysis

Abstract: Nimotuzumab is a blocking monoclonal antibody against epidermal growth factor receptor (EGFR). However, little is known about the safety and preliminary efficacy of nimotuzumab combined with concurrent chemoradiotherapy in locally advanced NPC patients. A total of 42 patients diagnosed between 2011 and 2013 were enrolled. Our results demonstrated 38 patients had a complete response (90.5%), 4 patients had a partial response (9.5%). And no patients had progressive disease at early treatment response evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
(29 reference statements)
4
40
0
Order By: Relevance
“…Compared with the CTX arm, significantly lower frequencies of severe skin reactions, mucositis and hypersensitivity infusion reactions were observed in the NTZ arm, both in the current analysis and in previous studies . This benefit could be attributed to the reduced affinity of NTZ, which results in binding with less avidity, compared to CTX, thus sparing healthy tissues and avoiding severe toxicities.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Compared with the CTX arm, significantly lower frequencies of severe skin reactions, mucositis and hypersensitivity infusion reactions were observed in the NTZ arm, both in the current analysis and in previous studies . This benefit could be attributed to the reduced affinity of NTZ, which results in binding with less avidity, compared to CTX, thus sparing healthy tissues and avoiding severe toxicities.…”
Section: Discussionsupporting
confidence: 46%
“…24,25 Compared with the CTX arm, significantly lower frequencies of severe skin reactions, mucositis and hypersensitivity infusion reactions were observed in the NTZ arm, both in the current analysis and in previous studies. [26][27][28] This benefit could be attributed to the reduced affinity of NTZ, which results in binding with less avidity, compared to CTX, 29 20 And recently, they further demonstrated addition of cisplatin, fluorouracil and docetaxel (TPF) induction chemotherapy to concurrent chemoradiotherapy could significantly improve failure-free survival in locoregionally Table 4. Interaction between treatment regimen status and other significant prognostic factors and its effect on disease-free survival, distant metastasis-free survival, loco-regional relapse-free survival and overall survival in all eligible 1,837 cases (Continued) advanced NPC.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%
“…In the current study, the rate of grade 3-4 mucositis was comparable between patients receiving CCRT plus NTZ (25.8%) and patients receiving CCRT only (19.4%). A recent retrospective analysis by Liu and colleagues 21 also concluded NTZ could be safely combined with CCRT for treatment of LA-NPC. However, Huang et al 12 reported 34.8% of patients receiving CCRT plus NTZ experienced grade 3 to 4 mucositis.…”
Section: Discussionmentioning
confidence: 97%
“…EGFR-blocking monoclonal antibodies may potentially exert encouraging effects in LA-NPC. Liu et al 21 examined 42 cases of LA-NPC treated with NTZ plus CCRT. The follow-up median was twenty-five months (ranging 7-44 months), where only two patients had died by last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…They further published another phase II study in which concurrent administration of CTX, CDDP, and IMRT demonstrated a feasible strategy against locoregionally advanced NPC 13. Furthermore, previous studies reported that NTZ combined with CCRT showed encouraging outcomes in the treatment of locally advanced NPC with no increased toxicity and an improved tolerance in the patients 14, 15. However, a direct comparison between CCRT alone and CTX/NTZ plus CCRT in NPC was lacking.…”
Section: Introductionmentioning
confidence: 99%